Analisis Perbandingan Beban Emisi Kendaraan Yang Terjadi Saat Keadaan Normal dan New Normal - Salsabila, Naura; Sulistiyorini, Rahayu; Putri Ofrial, Siti Anugrah; Herianto, Dwi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2021)
The Covid-19 virus has caused a decrease in transportation movement activities on the Z.A Pagar Alam road. Transportation movement activities due to the pandemic in which the government established a WFH (Work From Home) with this policy resulted in a reduction in the level of transportation modes so that it had a positive effect, namely reducing traffic congestion in the city center and also reducing air pollutants.In connection with the above problems, it is necessary to study the calculation of the emission load on the Z.A Pagar Alam road during the new normal period which can then be compared with the Z.A Pagar Alam emission load during the normal period, in order to find out how much the emission load changes on the R.A road. Kartini due to Covid-19.this study aims to determine the emission load of Pagar Alam Z.A during new normal conditions and during normal conditions. The results of this study indicate that there is a change in the emission load for each of the existing concentrates and the most significant is CO2 on the Z.A Pagar Alam road due to changes in vehicle volume that occur during normal and new normal conditions.